Propaganda, psychological warfare and communication research in the USA and the Soviet Union during the Cold War. (October 2016) - Nietzel, Benno
This article discusses the role of communication research in the Cold War, moving from a US-centered to a comparative-transnational point of view. It examines research on prop-aganda and mass communication in the United States and the Soviet Union, focusing not only on the similarities and differences, but also on mutual perceptions and transnational entanglements. In both countries, communication scientists conducted their research with its benefits for propaganda practitioners and waging the Cold War in mind. It has been suggested that after an initial period of close cooperation between politics and communication science, early expectations of the potential of systematic research for controlling the hearts and minds of people through propaganda started to fade. On both sides of the Iron Curtain, communication research eventually became a 'normal' scholarly discipline.